Intelligent Structures and Their Role in Creating Interactive Spaces - et. al., Molouk Sadat Mirkazemi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Urban planning has always been studied alongside its interaction with the surrounding environment. Yet, owing to the urban sprawl, the uncontrolled and poorly-managed population growth in the modern era, and the application of construction technology in a way inconsistent with the context, we are now witnessing an unrestricted growth in many urban areas of housing, commercial development, and roads over large expanses of land, with little concern for urban planning. Interactive architecture is a method that mostly deals with the interactive nature of architecture, humans, and the surrounding locations. Hence, the main quest in this discipline is to find ways to achieve, through innovative structures introduced as modern construction technologies, the ideal architecture and interactive spaces from the perspective of urban planning. In this regard, technological breakthroughs need to be reviewed and updated accordingly as an efficient tool in the processing method. One such breakthrough is intelligent structures that can respond appropriately and timely to the environment by receiving and processing environmental events and information through properties such as adaptability, selectivity, fast performance, automated performance, and dependency. The current study employs a descriptive-analytical design and archival methods to examine the interaction between the context and the intelligent structures and the benefits thereto. The findings indicated that, with its particular emphasis on human senses, culture, and context, construction technology, in addition to its primary role of implementing innovations in architectural spaces, can create interactive spaces, strengthen the spirit of social interactions, alleviate social problems and improve the quality of service-entertainment spaces.